2014
DOI: 10.29262/ram.v61i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia del síndrome DRESS

Abstract: El síndrome DRESS (exantema inducido por fármacos con eosinofilia y síntomas sistémicos) es una reacción idiosincrática (tipo B), que se distingue por eosinofilia periférica y síntomas sistémicos, como fiebre, exantema, linfadenopatía, hepatitis, linfocitos atípicos y elevación de enzimas hepáticas al menos dos veces su valor normal o incremento de la alanina aminotransferasa (ALT) >100 U/L. La incidencia es de 1 por cada 1,000 a 10,000 exposiciones y su mortalidad es de 10 a 20%. El tratamiento se basa en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…DRESS syndrome can recur; a systematic review that included 42 articles concluded that the average time to recurrence is 124 days, it usually presents with a higher fever and a higher number of eosinophils, generally attributed to another causal drug. In this study, it is mentioned that the survival of recurrences was 71% [4][5][6].…”
Section: Introductionmentioning
confidence: 72%
“…DRESS syndrome can recur; a systematic review that included 42 articles concluded that the average time to recurrence is 124 days, it usually presents with a higher fever and a higher number of eosinophils, generally attributed to another causal drug. In this study, it is mentioned that the survival of recurrences was 71% [4][5][6].…”
Section: Introductionmentioning
confidence: 72%